IMPLEMENTATION OF PROJECT-BASED LEARNING WITH AN EDU-ECOPRENEURSHIP FOCUS: STUDENTS’ PRACTICAL SKILLS AND THE QUALITY OF BAR SOAP MADE FROM USED COOKING OIL WITH PAPAYA EXTRACT - Aulia Nur Alfiannissa; Tri Wahyuni; Findiyani Ernawati Asih (Universitas Negeri Surabaya, 2026)
Used cooking oil is one of the household wastes that can be utilized as a raw material for solid soap production while supporting environmental sustainability efforts. This study explored the implementation of Project-Based Learning (PjBL) integrated with edu-ecopreneurship through a project involving the production of solid soap from used cooking oil with the addition of papaya extract. The study involved 72 tenth-grade students from the Laboratory Testing Analysis (APL) program at a vocational high school in Gresik and employed a quantitative descriptive approach with a one-shot case study design. Data were collected through observations of students’ practical skills and quality testing of the soap products, including pH value, residual alkali content, density, and foam stability. The observations showed that students generally demonstrated good practical skills during project implementation, particularly in preparing materials, following procedures, and applying laboratory safety practices. The soap produced by both classes exhibited relatively similar characteristics, with satisfactory density and foam stability; however, the pH values and residual alkali content indicated that the saponification process had not yet reached optimal conditions. The project provided opportunities for students to apply chemistry concepts through direct experience while utilizing waste materials with potential economic value, making learning activities more relevant to real-life environmental issues.